(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2021)
Training is considered as one of the determining factors for an individual to make a labor turnover. Fresh graduate workers are often associated with the labor turnover phenomenon. This research aims to study the relationship between the participation of fresh graduate workers in training with the probability of job-to-job and job-to-non-employment turnover in the first year after graduating from their highest education. This research used data from Survei Angkatan Kerja Nasional (Sakernas) - August 2019 with the multinomial logistic regression method to the fresh graduate workers aged 15-24 years old. The descriptive analysis result shows that job-to-job and job-to-non-employment turnover in the first year after graduating is a phenomenon that occurs in Indonesia, where the majority of fresh graduate workers do it voluntarily with the main consideration of the incompatibility of the working environment. The inferential analysis result shows that participation in training is positively correlated to the probability to make a job-to-job and job-to-non-employment turnover in the first year after graduating. Meanwhile, educational qualifications as college graduates and the type of work as white-collar workers reduce the probability to make a job-to-job and job-to-non-employment turnover in the first year after graduating from their highest education.